PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DI DAERAH TERPENCIL - Azhariadi Azhariadi; Ina Desmaniar; Zuliana Linggo Geni (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Remote Area Information and Communication Technology (ICT) Learning, Post Graduate Student Education Management Study Program, University of PGRI Palembang. This paper aims to describe the benefits of Information and Communication Technology-Based Learning in explaining the concept of learning, so that the delivery of information, in the teaching and learning process is more detailed, so that it is expected to help the process of understanding the material delivered more maximally and pleasantly. The purpose of Information and Communication Technology, as a solution to, develops the creativity of both educators and students. Information and communication technology-based learning is an effort to utilize the progress of Information and Communication Technology for the learning process, and functions as a tool not as the main subject, so that technology can help humans, in solving various problems in the real world, which is currently the foundation of the workforce, so that students have basic knowledge as the main capital to enter the workforce.